Odpowiedź :
Odpowiedź:
a)
(3 - 2x)/4 = (7 - 3x)/6
3/4 - 1/2x = 7/6 - 1/2x
-1/2x + 1/2x = 1 1/6 - 3/4
0 = 1 2/12 - 9/12 = 14/12 - 9/12 = 5/12
rownanie sprzeczne
nie ma rozwiazan
b)
(5 - x)/3 + 2x/3 = x/2
5/3 - 1/3x + 2/3x = 1/2x
1/3x - 1/2x = -1 2/3
2/6x - 3/6x = -5/3
-1/6x = -5/3 /*(-6)
x = 5/3 * 6 = 10
c)
1 - (2x + 7)/4 = 5 - 1/2x
1 - 1/2x + 7/4 = 5 - 1/2x
-1/2x + 1/2x = 5 - 1 - 1 3/4
0 = 5 - 2 3/4 = 2 1/4
rownanie sprzeczne
d)
2[5 - (x - 3)/2] + 2x = 0
2(5 - 1/2x + 3/2) + 2x = 0
10 - x + 3 + 2x = 0
x = -13
Szczegółowe wyjaśnienie: